If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) + -4x + -12 = 0 Reorder the terms: 4(-3 + x) + -4x + -12 = 0 (-3 * 4 + x * 4) + -4x + -12 = 0 (-12 + 4x) + -4x + -12 = 0 Reorder the terms: -12 + -12 + 4x + -4x = 0 Combine like terms: -12 + -12 = -24 -24 + 4x + -4x = 0 Combine like terms: 4x + -4x = 0 -24 + 0 = 0 -24 = 0 Solving -24 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 56-10x=12+12x | | 3(2x-5)=14 | | 6p=-7+5p | | (3x)(7x^4)= | | 2x+0.5x-2=-0.25x+2-0.5x | | h=-16t^2-20t+1100 | | 5(y+4)=4(y+5)-7y | | 3x+19=4x-10 | | -4r=5r+9 | | (x+2)(x+3)(x+4)=0 | | 3x-4+18=5x | | 4[x-6]+8=6x-8 | | -5n(r+7)=-52 | | -1+2y=-5+y | | 1100=-16t^2-20t+1100 | | 6-7x=7x-9x-29 | | 101y+2.50x=186.50 | | 360=0.75x | | 700-20x^2+40x=0 | | -10h+8=-8h | | 15x+10z+5= | | 32=8u+6(u+7) | | 3x^2+375=0 | | 7(6x-4)+1= | | 8-5(x+-4)=2x+-6 | | 3s+3=4a+5 | | 5y=21+2y | | 4x-45=-7(x-3) | | -3z=-4z+6 | | 5x+7(-4)=22 | | X-24=12(x) | | 6x+9x-22=66-7x |